SPEECH ABNORMALITY OF THE SCHIZOPHRENIC CHARACTER IN A BEAUTIFUL MIND MOVIE - Andani, Meri; Indah, Rohmani Nur (Annual International Conferences on Language, Literature, and Media, 2022)
This study looked at the speech abnormalities of John Nash, the main character of schizophrenia in the film A Beautiful Mind . He suffered from hallucinations and delusions that made him difficult to concentrate, remember, and speak or act regularly. This study had two objectives namely identifying Nash's speech disorder and describing the occurrence of his speech abnormality shown in the movie. The research design was descriptive qualitative by employing the theory of Liddle et al (2002) on categories of speech abnormality. The findings showed the perseveration of ideas, peculiar logic, looseness, and poverty of speech. Furthermore, the speech abnormality was caused by two main symptoms of schizophrenia, positive and negative symptoms, which altered John Nash's thoughts, language, and emotions. The schizophrenic character produced the most prolific perseveration and peculiar logic. He often said illogical things without supporting evidence, and often repeated his words. Through the findings, it was expected that readers and further researchers could gain better understanding on various types of schizophrenic speech disorders.